Pelvic Floor 3D Ultrasound of Women with a TVT, TVT-O, or TVT-S for Stress Urinary Incontinence at the Three-year Follow-up - Rodrigues, Claudinei A.; Bianchi-Ferraro, Ana Maria H. M.; Zucchi, Eliana Viana Monteiro; Sartori, Marair G. F.; Girão, Manoel J. B. C.; Jarmy-Di Bella, Zsuzsanna I. K. (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Objective Using three-dimensional ultrasound (3D-US), we aimed to compare the tape position and the angle formed by the sling arms in different techniques of mid-urethral sling insertion for the surgical treatment of stress urinary incontinence, three years after surgery. In addition, we examined the correlations between the US findings and the clinical late postoperative results.Methods A prospective cross-sectional cohort study of 170 patients who underwent a sling procedure between May 2009 and December 2011 was performed. The final sample, with US images of sufficient quality, included 26 retropubic slings (tension-free vaginal tape, TVT), 42 transobturator slings (tension-free vaginal tape-obturator, TVT-O), and 37 single-incision slings (tension-free vaginal tape-Secur, TVT-S). The images (at rest, during the Valsalva maneuver, and during pelvic floor contraction) were analyzed offline by 2 different observers blinded against the surgical and urinary continence status. Group comparisons were performed using the Student t-test, the chi-squared and the Kruskal-Wallis tests, and analyses of variance with Tukey multiple comparisons. Results Differences among the groups were found in the mean angle of the tape arms (TVT = 119.94°, TVT-O = 141.93°, TVT-S = 121.06°; p < 0.001) and in the distance between the bladder neck and the tape at rest (TVT = 1.65 cm, TVT-O = 1.93 cm, TVT-S = 1.95 cm; p = 0.010). The global objective cure rate was of 87.8% (TVT = 88.5%, TVT-O = 90.5%, TVT-S = 83.8%; p = 0.701). The overall subjective cure rate was of 83.8% (TVT = 88.5%, TVT-O = 88.5% and TVT-S = 78.4%; p = 0.514). The slings were located in the mid-urethra in 85.7% of the patients (TVT = 100%, TVT-O = 73.8%, TVT-S = 89.2%; p = 0.001), with a more distal location associated with obesity (distal: 66.7% obese; mid-urethra: 34% obese; p = 0.003). Urgency-related symptoms were observed in 23.8% of the patients (TVT = 30.8%, TVT-O = 21.4%, TVT-S = 21.6%; p = 0.630).Conclusions The angle formed by the arms of the sling tape was more obtuse for the transobturator slings compared with the angles for the retropubic or single-incision slings. Retropubic slings were more frequently located in the mid-urethra compared with the other slings, regardless of obesity. However, the analyzed sonographic measures did not correlate with the urinary symptoms three years after the surgery.
Keywords: urinary incontinence; ultrasonography; pelvic floor